KETERAMPILAN PROSES SAINS, KETERAMPILAN SOSIAL, KETERAMPILAN PSIKOMOTORIK, SERTA PENGUASAAN KONSEP SISWA SMA MELALUI PEMBELAJARAN BERBASIS INKUIRI - Rasmawan, Rahmat (Jurnal Pendidikan Matematika dan IPA, 2013)
The purpose of this research to describe scientific proccess skills, social skill, psychomotor skill and mastery concept student through inquiry based learning. Type of this research is descriptive with this subject 34 students of Science at 11th grade of SMAN 7 Pontianak. The measured of scientific procces skill by performance assessment test. The measured of the social skill by observation sheet of the social skill. The measured of the psychomotor skill by performance assessment test. The measured of the understanding concept by essay test about concept. The result shows that scientific proccess skills, social skill, psychomotor skill and mastery concept are 100%, 100%, 87% and 78% respectively. Based on the result, we can conclude that inquiry based learning could evolved scientific proccess skills and social skill students, trained to use tools of lab work and make students to understanding concept. Key Word: Scientific Proccess Skills, Social Skill, Psychomotor Skill, Mastery Concept, Inquiry Based Learning.